Proposed Marketing Strategy To Increase Sales For Indonesian Modestwear Retailer (Use Case: Toko Bani Adam) - An Nisaa Citra Hasanah; Ilma Aulia Zaim; Satya Aditya Wibowo (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
The purpose of this research is to propose the most accurate and suitable marketing strategy for Toko Bani Adam, including formulating the integrated marketing growth strategies based on the internal and external analysis, and to identify the appropriate step for implementing Toko Bani Adam the strategy. The suggested marketing strategy is extracted from the examination of internal and external data and is considered fit to increase sales for sustainable business. In research, data collection methods are carefully designed and implemented to obtain relevant and reliable data. Field research involved direct observation to gather the necessary data for the research. This method was used to obtain primary data, and the research was conducted on the activities of all research objects. To collect primary data, the author uses quantitative research by distributed questionnaires forms to Toko Bani Adam's customers and use qualitative conducted interview with the owner and management team. As the result, Toko Bani Adam, a Muslim apparel SME in Indonesia, operates in a dynamic political environment influenced by the rise of Islamic conservatism and increasing religious consciousness among the youth. Through the implementation of the 5A method, Toko Bani Adam aims to increase brand visibility, engage with customers, optimize marketing efforts, diversify marketing channels, and enhance the customer experience. This involves adapting marketing strategies based on thorough analysis, attracting customers through online presence and promotions, activating offline marketing activities, and continuously assessing the effectiveness of these efforts. By leveraging market insights, optimizing online platforms, participating in campaigns, and monitoring key metrics, Bani Adam can drive growth and success in a competitive market. Toko Bani will collaborate with social media agencies to maximize their presence on these platforms and achieve optimal results in terms of audience reach and engagement. Toko Bani Adam will also focus on offline marketing activities, such as in-store events and collaborations with local businesses or community organizations. This will help generate excitement and increase brand awareness among potential customers. Toko Bani Adam will launch promotional campaigns and create engaging content to encourage customer interaction and boost sales. They will also update their website with e-wallet payment options to facilitate convenient transactions for customers.